Inativação da Borrelia anserina pela ação da luz ultravioleta associada à riboflavina em soro sanguíneo de Gallus gallus domesticus - Dabus, Daniela Marques Maciel [UNESP] (2015)
Avian borreliosis is an acute septicemic disease caused by the spirochete Borrelia anserina, has a low incidence, however due to the growth of organic and rustic creations, greater concern for animal welfare and reducing the use of antibiotics in feed, there is concern about the emergence of disease outbreaks, which may cause economic losses. Thus, it becomes fundamental to search for alternative therapies, including, photodynamic therapy, such as the combination of ultraviolet (UV) light and riboflavin with the aim of controlling the disease. This study aimed to investigate the efficacy of treatment with riboflavin and UV light to inactivate or eliminate B. anserina from serum laying hens by diagnostic and laboratory tests and to check to the host immune response. The experiment was conducted in two stages. The first one was the in vivo step composed of 42 chickens, divided into seven groups of six birds: Group 1 (health); Group 2 (disease) inoculated with the serum parasitized by Borrelia anserina; Group 3 (immunosuppressant) receiving methylprednisolone; Group 4 (UV light) which received parasitized saline treated with UV light; Group 5 (riboflavin) which received parasitized serum treated with riboflavin; Group 6 (solvent group) parasitized receiving saline treated with 0.9% sodium chloride; Group 7 (treated) which received positive serum for B. anserina treated with ultraviolet light associated with riboflavin. The secund one was the in vitro stage performed with cell culture plates, equally divided in vivo step. It was observed that the treatment did not show expected results in the inactivation or complete elimination of the agent. However, one bird from the treated group survived and showed clinical and laboratory recovery, presenting spirochetemia at the time 11 and qPCR positive at the time...